ChemInform Abstract: MgCl2·6H2O Catalyzed Highly Efficient Synthesis of 2‐Substituted‐1H‐benzimidazoles. Issue 36 (September 2015) - Ghosh, Pranab; Subba, Raju
Abstract A new facile protocol is reported for the condensation of 1, 2‐phenylenediamine with aryl‐ and hetaryl aldehydes to produce benzimidazoles.